Bacterial strains found in the soils of a municipal solid waste dumping site facilitated phosphate solubilization along with cadmium remediation. (January 2022) - Sahu, Sudha; Rajbonshi, Manas Protim; Gujre, Nihal; Gupta, Manish Kumar; Shelke, Rahul G.; Ghose, Anamika; Rangan, Latha; Pakshirajan, Kannan; Mitra, Sudip
Abstract: Phosphate solubilizing bacteria (PSB) that can withstand high cadmium (Cd) stress is a desired combination for bioremediation. This study evaluated the Cd bioremediation potential of four PSB strains isolated from the contaminated soils of a municipal solid waste (MSW) discarding site (Guwahati, India). PSB strains were cultured in Pikovskaya (PVK) media, which led to higher acid phosphatase (ACP) activity and the release of organic acid. Optical density (OD) measurements were performed to determine the growth pattern of PSB; furthermore, Cd uptake by PSB was evaluated using infrared spectroscopy (IR) and X-Ray Diffraction (XRD) analyses. The 16S rRNA taxonomic analysis revealed that all the four promising PSB strains belonged to either Bacillus sp. or Enterobacter sp. One strain (SM_SS8) demonstrated higher tolerance towards Cd (up to 100 mg L −1 ). Flow cytometry analysis revealed 70.92%, 46.93% and 20.4% viability of SM_SS8 in 10, 50 and 100 mg L −1, respectively in PVK media containing Cd. This study has therefore substantiated the bioremediation of Cd from polluted soil by the PSB isolates. Thus, experimental results revealed a potential combo benefit, phosphate solubilization along with Cd remediation. Graphical abstract: Image 1 Highlights: Isolated four phosphate solubilizing bacteria (PSB) from MSW dumping site's soil. One of the isolated PSB strains (SM_SS8) demonstrated significant Cd tolerance. Flow cytometry analysis revealed that SM_SS8 strain can resist 100 mg L −1 Cd stress. Intracellular accumulation of Cd in PSB was confirmed by FTIR and XRD analyses.